Clinical Trials Explained : a Guide to Clinical Trials in the NHS for Healthcare Professionals. - Kerr, David J. (John Wiley & Sons, 2007)
What will happen during and after a clinical trial?.; How will a trial affect my quality of life?.; What are the benefits and risks of a trial?.; What does giving consent mean and what will it involve?.; Will I incur costs during and because of the trial?. These are the questions that should be raised every time a health care professional talks through with a patient the pros and cons of entering a clinical trial. Clinical Trials Explained has been designed in consultation with doctors and patients who have taken part in trials, providing an essential and detailed guide to the clinical trials.